1973
DOI: 10.1128/jvi.12.1.114-123.1973
|View full text |Cite
|
Sign up to set email alerts
|

Antigenic Determinants of Infective and Inactivated Human Rhinovirus Type 2

Abstract: Treatment of human rhinovirus type 2 (HRV 2) virions at pH 5, at 56 C or in 2 M urea, produces one or both of two types of subviral particles. These subviral particles sediment at 135S or at 80S and both share what have been designated as C-antigenic determinants; the determinants of native virions have been designated D. These sets of determinants have been contrasted by the techniques of immunodiffusion, complement fixation, and serum blocking, and the results indicate that many or most of the D-determinants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
38
0

Year Published

1987
1987
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 79 publications
(42 citation statements)
references
References 25 publications
4
38
0
Order By: Relevance
“…It is of note that 135S particles prepared according to ref. [2] exhibited an electrophoretic net mobility = −16.6 × 10 −9 m 2 /Vs (Table 1) in CE, a value in good accordance with the electrophoretic net mobility of AI particles as stated above. However, our initial experiments demonstrated that incubation at 56ЊC for 10 min (Fig.…”
Section: Characterization Of Intermediate Ai Particlessupporting
confidence: 85%
“…It is of note that 135S particles prepared according to ref. [2] exhibited an electrophoretic net mobility = −16.6 × 10 −9 m 2 /Vs (Table 1) in CE, a value in good accordance with the electrophoretic net mobility of AI particles as stated above. However, our initial experiments demonstrated that incubation at 56ЊC for 10 min (Fig.…”
Section: Characterization Of Intermediate Ai Particlessupporting
confidence: 85%
“…In the course of the present manuscript we focused on AI intermediates. From the sum of the experimental results concerning the particle composition we find AI particles of our research work indistinguishable from subviral A particles of rhinovirus uncoating as previously described [2]. Additional experiments targeted possible factors influencing the formation of intermediate AI particles as well as its antigenicity.…”
Section: Introductionsupporting
confidence: 73%
“…After spin SEC, the electropherogram allows the conclusion that AI particles possess indeed only three viral proteins (VPs): VP4 from the virion is missing (dashed line, highlighted area). This together with detected RNA allows the conclusion that intermediate AI particles are identical with 135S intermediates as described in 1973 by Lonberg-Holm and Yin [2]. Injection and electrophoresis were as in Fig.…”
Section: Rna Content Of Ai Particlessupporting
confidence: 62%
See 1 more Smart Citation
“…These non-infectious particles which lack the VP4 polypeptide can also be obtained by in vitro treatment of the virion with acid, alkali, heat or urea (Lonberg-Holm and Yin, 1973). As most of the properties of "A particles" are very similar to those of the dense particles reported here, dense partides may be equivalent to "A particles".…”
Section: Discussionmentioning
confidence: 67%